1998
DOI: 10.1097/00002030-199803000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of zidovudine use on risk and risk factors for perinatal transmission of HIV

Abstract: Perinatal HIV transmission risk has declined with increasing perinatal zidovudine use and changes in other factors. Further reduction in transmission for women taking zidovudine may be possible by reducing the incidence of other potentially modifiable risk factors, such as long duration of membrane rupture and prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…Access to neonatal intensive care units in the United States ensures that perinatal morbidity is not significant for an infant born at у32 weeks of gestation to an HIV-negative woman. This is also valid for an infant delivered at the same gestational age to an HIVinfected woman; however, despite the lack of morbidity secondary to prematurity, preterm delivery itself may increase the risk of perinatal transmission 2-3-fold [13][14][15]. To our knowledge, this is the largest single-site study and the only large study reported to date that can account for both the completeness of its data and its management protocols and is representative of HIV-infected pregnant women in the United States; the study is relatively unique because of the autonomous management by a maternal-fetal medicine team.…”
Section: Discussionmentioning
confidence: 99%
“…Access to neonatal intensive care units in the United States ensures that perinatal morbidity is not significant for an infant born at у32 weeks of gestation to an HIV-negative woman. This is also valid for an infant delivered at the same gestational age to an HIVinfected woman; however, despite the lack of morbidity secondary to prematurity, preterm delivery itself may increase the risk of perinatal transmission 2-3-fold [13][14][15]. To our knowledge, this is the largest single-site study and the only large study reported to date that can account for both the completeness of its data and its management protocols and is representative of HIV-infected pregnant women in the United States; the study is relatively unique because of the autonomous management by a maternal-fetal medicine team.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, elective cesarean section has also been shown to reduce the risk of mother-tochild transmission of HIV. These preventive strategies, resulting in dramatic declines in pediatric HIV and AIDS in the USA and Europe, [2][3][4] are costly options, and thus are not yet realistic solutions for resource-poor countries like South Africa.…”
Section: Socio-economic and Cultural Status Of Women In South Africanmentioning
confidence: 99%
“…The successful implementation of antiretroviral therapy for HIV positive pregnant women and their infants has led to dramatic reductions in pediatric AIDS in the United States and Europe. [2][3][4] The other (bleaker) side is quite pessimistic. In the developing world, which bears the burden of more than 95% of the world's HIV infection, the HIV/AIDS pandemic continues to rage on and there is little hope for those afflicted.…”
Section: Introductionmentioning
confidence: 99%
“…If in the 48 th h of newborn's life the test yields a positive result (pointing to presence of the pathogen) the infection took place inside the uterus, when the result of the test is negative in the 48 th h but positive between the 7 th and 90 th day the infection developed most probably during delivery [9].…”
Section: Diagnosismentioning
confidence: 99%